2004
DOI: 10.1002/net.10107
|View full text |Cite
|
Sign up to set email alerts
|

On some properties of suboptimal colorings of graphs

Abstract: Starting from the trivial observation that, in any optimal coloring of a graph, there always exists a node v such that its neighborhood N(v) contains all colors, we examine related properties in suboptimal colorings (i.e., those using more than (G) colors, where (G) is the chromatic number). In particular, we show that, in any ((G) ؉ p)coloring of G, there is a node v such that its generalized neighborhood N q (v) with q ‫؍‬ max{2p ؊ 1, 2} contains (G) colors for p ≥ 1. Additional properties of ((G) ؉ p)colori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…We shall now establish a bound on ( , p) which will strengthen a result given in [2]. This can be formulated by stating ( , p) p/2 + 1 for all and p. Notice that for p = 0, Theorem 8 reduces to Proposition 3.…”
Section: A Property Of Coloringsmentioning
confidence: 77%
See 4 more Smart Citations
“…We shall now establish a bound on ( , p) which will strengthen a result given in [2]. This can be formulated by stating ( , p) p/2 + 1 for all and p. Notice that for p = 0, Theorem 8 reduces to Proposition 3.…”
Section: A Property Of Coloringsmentioning
confidence: 77%
“…By construction, we have K 1 (v i,{j,k} )={i, j, k}. In [2], we have shown that (pentaK 3,3 )= 4. We shall now prove that pentaK 3,3 has a minimum number of vertices.…”
Section: An Lr-colorable Graph: the Pentak 33mentioning
confidence: 92%
See 3 more Smart Citations